Preliminary Phytochemical Analysis and Antimicrobial Activity of Some Weeds collected from Marathwada Region - JA, Dhole; NA, Dhole; KD, Lone; SS, Bodke (Journal of Research in Biology, 2011)
The aqueous and ethanolic extracts of selected weeds such as Portulaca oleracea L. (Portulaceae), Cardiospermum helicacabum L. (Sapindaceae), Euphorbia hirta L. (Euphorbiaceae), Crotalaria retusa L. (Fabaceae) and Euphorbia heterophylla L. (Euphorbiaceae) were screened for phytochemical analysis and antimicrobial activity. The antimicrobial activities were tested against two gram-positive bacteria (Bacillus subtilis, Staphylococus aureus), one gram-negative bacterium (Pseudomonas aeruginosa) and a mould Aspergillus niger by agar diffusion method. The phytochemicals like alkaloids, saponins, tannins, cardiac glycosides, steroids and flavonoids are investigated from plant samples. Tannins, steroids and flavonoids were absent in the Cardiospermum helicacabum L. Remarkable antibacterial activity was observed in the aquous and ethanolic (root and leaves) extracts of Portulaca oleracea L. while Cardiospermum helicacabum L. showed no results in same experimental conditions as compared with standard antibiotics. The weed Euphorbia hirta L possess significant antifungal activity as compared to nystatin used as a standard antifungal agent